Les indicateurs anthropométriques pour évaluer l'état nutritionnel des individus et des populations - Michel Garenne (Fondation pour les études et recherches sur le développement international (FERDI), 2014)
The paper presents the most common anthropometric indicators of nutritional status for individuals and for populations. It provides tips to evaluate their pertinence for comparing two populations and for measuring long-term trends in nutritional status. It covers at the same time issues of malnutrition (nutritional deficit) in developing countries, and issues of over-nutrition and obesity (nutritional surplus) which became a global public health issue. It is illustrated by examples drawn from European countries, from North-American countries, and from African countries. It aims at providing an overview for non-specialist investigators, and in particular for economists, demographers, statisticians and other social scientists interested in measuring nutritional status.
Keywords: 330